Trapped in a maze : how social control institutions drive family poverty and inequality - Paik, Leslie (University of California Press, 2021)
"Trapped in a Maze provides a window into families' lived experiences in poverty by looking at their complex interactions with institutions such as welfare, hospitals, courts, housing, and schools. Families are more intertwined with institutions than ever as they struggle to maintain their eligibility for services and face the possibility that one institutional involvement could trigger other types of institutional oversight. Many poor families find themselves trapped in a multi-institutional maze, stuck in-between several systems with no clear path to resolution. By showing families' complex and often unpredictable journeys in this maze, this book reveals the limits of the formal rationality by which these institutions ostensibly function and demonstrates how multi-institutional involvement serves to perpetuate the conditions of poverty that these families are fighting to escape"--